Singapore : a success story without a soul - Nur Diyanah Mohd Azmi (2014)
The Singapore success story is the product of the pervasive survivalist mentality that has been inculcated in Singaporean citizens by the Singapore government. This success is strongly motivated by a desire to overcome Singapore’s two most acute weaknesses that include: (i) the lack of natural resources that could help facilitate its economic progress and (ii) the scarcity of land. This desire resulted in the nation’s meteoric rise; from a British colony to an independent nation that has achieved first world nation status . In order to overcome the aforementioned weaknesses, the government relentlessly promotes a survivalist mentality. However, this success comes at a high price – the cost of the nation’s soul. The Singapore soul here refers to the culture and identity of the nation and its people. This thesis will justify the idea that Singapore is a success story without a soul through the exploration of the individual’s incapacity to reach the stage of self-actualisation and the treatment of space in the nation with references Goh Poh Seng’s Dance of the Moths, Suchen Christine Lim’s Rice Bowl and The River’s Song.